Complete Cuboidal Sets in Axiomatic Domain Theory (Extended Abstract) - Fiore, Marcelo P; Plotkin, Gordon; Power, John (My University, 2003)
We study the enrichment of models of axiomatic do- main theory. To this end, we introduce a new and broader notion of domain, viz. that of complete cuboidal set, that complies with the axiomatic requirements. We show that the category of complete cuboidal sets provides a general notion of enrichment for a wide class of axiomatic domain-theoretic structures.
Keywords: Laboratory for Foundations of Computer Science